2011
DOI: 10.1021/ja200231v
|View full text |Cite
|
Sign up to set email alerts
|

Phosphine-Catalyzed Annulations of Azomethine Imines: Allene-Dependent [3 + 2], [3 + 3], [4 + 3], and [3 + 2 + 3] Pathways

Abstract: In this paper we describe the phosphine-catalyzed [3 + 2], [3 + 3], [4 + 3], and [3 + 2 + 3] annulations of azomethine imines and allenoates. These processes mark the first use of azomethine imines in nucleophilic phosphine catalysis, producing dinitrogen-fused heterocycles, including tetrahydropyrazolo-pyrazolones, -pyridazinones, -diazepinones, and -diazocinones. Counting the two different reaction modes in the [3 + 3] cyclizations, there are five distinct reaction pathways—the choice of which depends on the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
95
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 302 publications
(96 citation statements)
references
References 112 publications
0
95
0
1
Order By: Relevance
“…85 The reaction proceeds smoothly under mild reaction conditions, furnishing a broad range of 1,2-dinitrogen-containing heterocycles 152 in moderate to excellent yield. In the use of enantioenriched chiral phosphines 153, the asymmetric version of this reaction has been realized, giving the corresponding cycloadduct in 56% yield with 89% ee.…”
Section: Catalytic 13-dipolar Cycloadditions Of Cyclic Azomethine Immentioning
confidence: 98%
“…85 The reaction proceeds smoothly under mild reaction conditions, furnishing a broad range of 1,2-dinitrogen-containing heterocycles 152 in moderate to excellent yield. In the use of enantioenriched chiral phosphines 153, the asymmetric version of this reaction has been realized, giving the corresponding cycloadduct in 56% yield with 89% ee.…”
Section: Catalytic 13-dipolar Cycloadditions Of Cyclic Azomethine Immentioning
confidence: 98%
“…Other compounds with unsaturated bonds, such as allenoates [35][36] and activated alkenes, [37] were evaluated as well. Uncatalyzed or PA C H T U N G T R E N N U N G (t-Bu) 3 -catalyzed [3+2] cyclization of azomethine imine ylides 56 and 78 were described by Kwon 35 and Guo, [36] respectively.…”
Section: A C H T U N G T R E N N U N G [3+2] Cyclization Of N-imide Ymentioning
confidence: 99%
“…Uncatalyzed or PA C H T U N G T R E N N U N G (t-Bu) 3 -catalyzed [3+2] cyclization of azomethine imine ylides 56 and 78 were described by Kwon 35 and Guo, [36] respectively. The transformation showed high efficiency and excellent functional group tolerance (Scheme 23).…”
Section: A C H T U N G T R E N N U N G [3+2] Cyclization Of N-imide Ymentioning
confidence: 99%
See 1 more Smart Citation
“…In 2003, Zhu et al firstly reported the [4 + 2] annulation reaction of allenoates and N-tosylbenzaldimines to form functionalized tetrahydropyridines [25], which leads to the large-scale applications of the phosphinecatalysts. Since the pioneer work of Lu and Kwon are reported, many efforts have been devoted to improve and develop various kinds of the phosphine-catalyzed reactions [2,12,[26][27][28][29][30][31][32][33][34][35][36][37][38][39]. In 2009, Kwon reported phosphine-catalyzed [3 + 3] annulations of aziridines and allenoates to get azidirines in room temperature [40].…”
Section: Introductionmentioning
confidence: 99%